Value creation in public procurement of innovation: a case of engaging start-ups by a local government. Issue 4 (4th July 2022) - Talebi, Alireza; Rezania, Davar; Bragues, George
ABSTRACT: We examine a recent theory by Austin and Seitanidi which proposes a framework for analysing value creation in inter-organisational collaborations. Le Pennec and Raufflet offer an empirical examination of Austin and Seitanidi's model and provide a critical path in the form of a pyramid among diverse types of value created during collaborative processes. Associational value is the base of the pyramid, followed by transferred resource, interactional, and synergistic value. We examine a case of public procurement of innovation in which a local government worked with start-ups to address civic issues. We identify what types of value are created in public-purpose collaborations between a local government and start-ups, and how those values interact with each other. The study extends Le Pennec and Raufflet's pyramid by providing evidence of a dynamic path in the creation of diverse types of value in a collaborative process of public procurement of innovation where start-ups are engaged.